Effect of Oral Placement and Expressive Therapies on Speech Intelligibility of Adolescents with Articulation Disorder - Amodu, Temitope Adebisi; Osisanya, Ayodele; Dada, Oluseyi Akintunde; Petters, Janet Sunday; Uzor, Margaret Okwuonu; Sarimiye, Francis Kibai; Orovwigho, Andrew Oghenerukevwe; Mbaekwe, Uzoamaka Nneka; Etim, Victoria Enefiok; Ngwu, Maria Enemeba; Nnamani, Ololade Olayinka; Orim, Samuel Orim (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Intelligible speech is vital to every adolescent's life, but this skill can be confounded with the presence of articulation disorder. Meanwhile, studies have been conducted using different therapies to improve speech intelligibility. This study investigated the effect of oral placement and expressive therapies on speech intelligibility among adolescents with articulation disorders. The study adopted a pretest-posttest, control group, quasi-experimental research design with a 3x2x2 factorial matrix. Three special centers were randomly selected, and purposive sampling was used in selecting 60 adolescents having articulation disorders comprising 34 males and 26 females. These adolescents were randomly assigned to Experimental Group 1 (n= 22), Experimental Group 2 (n= 21), and Control (n= 17). Speech Intelligibility Assessment Scale (r=0.92) was the instrument used for the study. Participants in the experimental groups were exposed to the oral placement and expressive therapeutic treatments, while those in the control groups were sensitized to a placebo. Three hypotheses were tested at a 0.05 level of significance, while data were analyzed using Analysis of Covariance (ANCOVA), mean scores, and Bonferroni Post Hoc Test. Findings revealed that there was a significant main effect of treatments F(2,56) = 112.52; p <0.05 (oral placement therapy, expressive therapy, and control group with placebo), and also a significant interaction effect of treatments, gender, and age F(2, 47) = 7.37; p <0.05 on speech intelligibility of adolescents with articulation disorders despite the presence of placebo. Oral placement and expressive therapies were effective in managing the speech intelligibility of adolescents with articulation disorders. Therefore, speech therapists should adopt these therapeutic interventions in rehabilitating adolescents with articulation disorders.